The line y = m x + 1 touches the curve y = − x 4 + 2 x 2 + x at two points P ( x 1 , y 1 ) and Q ( x 2 , y 2 ) . Find the value of ( x 1 2 + x 2 2 + y 1 2 + y 2 2 )
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
same method....
Great solution!!
Good Method
According to the question we can say that :
− x 4 + 2 x 2 + x = m x + 1 has solutions x 1 , x 1 and x 2 , x 2 .
⟹ x 4 − 2 x 2 + ( m − 1 ) x + 1 = ( x − x 1 ) 2 ⋅ ( x − x 2 ) 2
On comparing coefficients, we get : x 1 = 1 , x 2 = − 1 and m = 1
Putting values of x 1 , x 2 in the equation of curve, we get y 1 = 2 , y 2 = 0 .
Hence x 1 2 + x 2 2 + y 1 2 + y 2 2 = 6 .
enjoy !
Same method sir , +1!
Also sir , I think there's a small typo in the 2 n d line of your solution , y 1 , y 2 are missing and instead you have mentioned the x coordinates .
Log in to reply
That's not a typo, It will be the same as written x 1 , x 1 , x 2 , x 2 means x 1 is two-times repeated root and same with x 2 .
Log in to reply
Oh !! I have understood it now sir. I had read it in haste, sorry for troubling you .
Well I did a bit differently . I equated the slopes to get a cubic and the equations to get a quartic. The two must have two common solutions. Hence the answer
The point of intersection of two curves is given by equating the line and curve. So , x 4 − 2 x 2 + ( m − 1 ) x + 1 = 0 At these points of intersection the slopes of the two curves are equal as well, So 4 x 3 − 4 x + m − 1 = 0 The two equations must have two common solutions. x = + 1 , − 1 satisfies them hence the answer
m=1 ; x= 1,-1
Problem Loading...
Note Loading...
Set Loading...
Since the line y = m x + 1 touches the curve y = − x 4 + 2 x 2 + x at P ( x 1 , y 1 ) and Q ( x 2 , y 2 ) (see above), at these two points the following equations are satisfied.
⎩ ⎨ ⎧ y = − x 4 + 2 x 2 + x = m x + 1 d x d y = − 4 x 3 + 4 x + 1 = m . . . ( 1 ) . . . ( 2 )
E q 1 − E q . 2 × x : ⇒ 3 x 4 − 2 x 2 = 1 ⇒ ( 3 x 2 + 1 ) ( x 2 − 1 ) = 0
⇒ x = ± 1 ⇒ { x 1 = 1 x 2 = − 1 ⇒ y 1 = − 1 + 2 + 1 = 2 ⇒ y 1 = − 1 + 2 − 1 = 0
⇒ x 1 2 + x 2 2 + y 1 2 + y 2 2 = 1 + 1 + 4 + 0 = 6